Comparison of rhomboid intercostal nerve block, erector spinae plane block and serratus plane block on analgesia for modified radical mastectomy: A prospective randomised controlled trial. Issue 10 (2nd July 2021) - Jiang, Chen‐Wei; Liu, Fen; Zhou, Qinghe; Deng, Wei
Abstract: Background and objectives: Breast cancer is one of the most common malignant tumours among women. In this study, we compared the analgesic efficacy of ultrasound (US)‐guided rhomboid intercostal nerve block, erector spinae plane (ESP) block and serratus plane block (SAB) after modified radical mastectomy (MRM) of unilateral breast cancer. Methods: This study involved a double‐blind clinical trial that was carried out in the Affiliated Hospital of Jiaxing University on 23 September 2020. The inclusion criteria were the following: The American Society of Anesthesiologists (ASA) grade needed to be 1‐2, the patients needed to be between 18 and 80 years old, and MRM needed to be proposed in our hospital. The exclusion criteria were patients with contraindications related to nerve block. Ninety patients were randomly divided into three groups receiving US‐guided SAB, ESP block and rhomboid intercostal block (RIB). All groups received 20 mL 0.5% ropivacaine. Within 24 hours after the operation, the patients received an intravenous injection of tramadol 1‐2 mg/kg in the surgical ward for pain relief. Results: The dosage of tramadol 24 hours after the operation in the RIB (269.67 ± 48.75 mg) and ESP block groups (273.67 ± 36.90 mg) was significantly lower than that in the SAB group (314.33 ± 18.88 mg) ( P < .001). There was no statistical difference in tramadol consumption between the ESP block and RIB groups within 24 hours ( P = .676). The numerical rating scale (NRS) scores in the ESP block and RIB groups at 0.5, 1, 3, 6, 12, 18 and 24 hours after the operation once patients were active were significantly lower than that in the SAB group ( P < .05 for all comparisons); however, the NRS scores of the RIB and ESP block groups did not differ significantly within 24 hours after surgery when patients were active. Conclusions: US‐guided rhomboid intercostal block (US‐RIB) and ESP block can effectively reduce the dosage of tramadol within 24 hours after MRM, and they can effectively relieve pain within 24 hours after MRM compared with SAB.